An Algorithm for Subpixel Snow Mapping: Extraction of a Fractional Snow-Covered Area Based on Ten-Day Composited AVHRR\/2 Data of the Qinghai-Tibet Plateau - Zhu, Ji; Shi, Jiancheng (IEEE geoscience and remote sensing magazine, 2018)
Advanced very-high-resolution radiometer (AVHRR)/2 sensors lack the e 1.6-nm channel used by Moderate Resolution Imaging Spectroradiometer (MODIS) and AVHRR/3; consequently, the subpixel snow-mapping algorithms for MODIS and AVHRR/3 data cannot be introduced into the subpixel snow mapping for AVHRR/2 data. To formulate subpixel snow mapping for AVHRR/2 data, in this research we determined an algorithm for subpixel snow mapping using ten-day composited AVHRR/2 data from the Qinghai-Tibet Plateau and extending moderate-resolution fractional snow-covered-area data to more than 30 years.